Exploring the level of knowledge, attitude and practice of emergency contraceptive among college students of Banepa Municipality of Kavre District. - Dahal, Srijana (2015)
SUMMARY: Emergency contraception, or postcoital contraception is a hormonal contraception which is used within 72 hours to 120 hours after unprotected and unsafe sexual intercourse for the prevention of unintended pregnancies. It is intended for emergency use following unprotected intercourse, contraceptive failure or misuse (such as forgotten pills or torn condoms), rape or coerced sex. Teenage pregnancy, unplanned and unwanted pregnancy is growing worldwide problem associated with the poor pregnancy outcome which is more common in developing country like Nepal. Young people in general are sexually active and tertiary institutions' students form a significant high-risk group in any society. The youth in this age group are most often at the beginning of exploration of their sexuality, very often free of parental guidance, under great peers influence, and often indulging in alcohol or other influential illegal substances. Tertiary institutions' students on the other hand, by virtue of their level of education, probably form a group in any community, which should have an overall higher level of awareness of available methods of contraception, including that of EC. This study sought to assess the knowledge and attitude towards EC, and as well to determine the prevalence of emergency contraceptive use among students. Emergency Contraceptive Pills (ECPs) have not received significant attention and women's access to this type of contraceptive continues to be limited. Study on ECPs among college students can play a crucial role in family planning programs, providing a safe method of avoiding unwanted pregnancy after unprotected sexual intercourse, and a bridge to the practice of regular contraception. Objective:The general objective of this research was to explore the level of knowledge, attitude and practices of emergency contraceptive pills among college students of Banepa Municipality of Kavre district. Methodology:Descriptive cross sectional study design was used. Target population was bachelor level students which includes both married and unmarried youths. Total 10 colleges of Banepa Municipality were selected. Simple random sampling was done and 4 colleges were selected randomly for the data collection. Total sample size was 131 including nonresponseerrors. Pretesting was done on similar setting to check the validity, consistency, and errors so that necessary modifications on tools can be done. Structured anonymous SAQ was used for the collection of necessary quantitative data. Written informed consent was taken prior to the collection of data from participants. Ethical approval from evaluation committee of CiST College was also taken. Side by side ethical approval from NHRC was also taken. Collected data and information was tabulated in Excel and analyzed by using SPSS version 22. Analyzed information was presented in the college in the form of mean, median, frequency, table, graphs, charts, histogram pie-charts etc. as per the nature of the data. Thoroughly review of literature conducted during this study. Findings:The study revealed that the median age of the respondents was 21 years. Among them56.5% were female. 90% of the respondents had heard about ECP which was higher than the level fond among university students in Cameroon (63%), Ghana (43.2%), and Katmandu (66%). However, it was low compared to the university students, for example, in the USA (94%). Around one-third of the respondents had stated that it is available in pharmacy. More than half of the respondents were aware about its right purpose of using ECP but, 42.4%, and 3.4% had wrong knowledge that it is used for FP purpose and for abortion respectively .Two- third of the respondents were aware that ECP should be taken within 24 hours for its effectiveness which was also a good outcome of this study. The study discovered that 54.2% of the total respondent are sexually active which was higher than the study done in the Lekhnath Municipality (21.1%). .Among the sexually active 64 respondents (54.2%), 65.1% had ever used ECP after the sexual intercourse which is higher than the study done in West Bengal(26.2%). Use of ECP rate of our study is also higher than that of the study done in Lekhnath Municipality, where 28.1% had used ECP. Similarly, a study done in Nigeria showed 27.6%used ECP which is also very lower than that of our study[19]. More than 80% had sexual relationships with their boyfriend or girlfriend. There was strong association between age and heard about ECP, marital status and sex experience, but there was no association found between age and sex experience. Conclusion: Even though majority of the respondents had heard about ECP, many of them had misconception about it. Also, unmarried youths were highly engaged in sexualexperience since early age which can create lots of health problems regarding unintended pregnancy, unsafe abortion and abortion related complications. Key Words:Knowledge, Attitude, Practice, bachelor Level Students, ECP and its use